2018
DOI: 10.1002/adma.201801787
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Performance of IV–VI Compounds with Octahedral‐Like Coordination: A Chemical‐Bonding Perspective

Abstract: Thermoelectric materials provide a challenge for materials design, since they require optimization of apparently conflicting properties. The resulting complexity has favored trial-and-error approaches over the development of simple and predictive design rules. In this work, the thermoelectric performance of IV-VI chalcogenides on the tie line between GeSe and GeTe is investigated. From a combination of optical reflectivity and electrical transport measurements, it is experimentally proved that the outstanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
99
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 63 publications
4
99
0
1
Order By: Relevance
“…A larger band anisotropy is beneficial for the thermoelectric performance, since it allows to maximize thermoelectric performance. A systematic study of the band anisotropy and power factor for (GeTe) 1− x –(GeSe) x solid solution may help answer this question . Figure a shows that with increasing the content of GeSe, the ternary alloy undergoes a phase transition from rhombohedral to hexagonal at x > 0.65, while the pure GeSe phase is orthorhombic.…”
Section: Band Engineering By Tuning the Chemical Bondmentioning
confidence: 99%
See 4 more Smart Citations
“…A larger band anisotropy is beneficial for the thermoelectric performance, since it allows to maximize thermoelectric performance. A systematic study of the band anisotropy and power factor for (GeTe) 1− x –(GeSe) x solid solution may help answer this question . Figure a shows that with increasing the content of GeSe, the ternary alloy undergoes a phase transition from rhombohedral to hexagonal at x > 0.65, while the pure GeSe phase is orthorhombic.…”
Section: Band Engineering By Tuning the Chemical Bondmentioning
confidence: 99%
“…Then, the trend of the effective mass tensor with respect to changes in bond parameters can be inferred from the corresponding changes in the bandwidths along the principal axes. This description has been successfully implemented by means of s–p 3 next‐nearest‐neighbor tight‐binding model . It has been shown that increasing s–p mixing between cation s and anion p states increases the bandwidth along Γ–L with respect to the one along L–W, hence reducing the ratio between longitudinal and transverse effective masses .…”
Section: Band Engineering By Tuning the Chemical Bondmentioning
confidence: 99%
See 3 more Smart Citations